Patriotism and National Symbols in Russian and Ukrainian Elections - Grechanaya, Tamara (2024)
How do political parties leverage patriotic appeals in their online campaigning within the context of autocracies and hybrid regimes? This study delves into the digital campaign strategies deployed by political parties during the most recent legislative elections in Russia (2021) and Ukraine (2019). In light of the armed conflict between Russia-backed separatists and Ukrainian forces in the eastern area of Ukraine, war-related themes and patriotic rhetoric emerged as pivotal concerns for politicians in both countries. The “rally around the flag” phenomenon posits that, in times of crisis, citizens often experience an intensified sense of national identity and patriotic fervor. Consequently, references to patriotism and related topics may evoke positive responses and prove instrumental for politicians during elections, serving to engage, mobilize, and attract voters. Drawing on a manual content analysis of the underlying communication strategies, we assessed whether parties’ reference to patriotic gestures and symbols or their attention to related policy topics (defense, war and military conflicts, and foreign policy and international relations) yielded an increased level of user engagement. Our findings reveal that references to patriotic symbols engendered increased user engagement within the Russian context, albeit without significantly affecting the engagement of Ukrainian voters. The latter tended to exhibit greater engagement with posts addressing defense and foreign policy matters though. Interestingly, Russian parties conspicuously avoided war-related topics, while Ukrainian voters displayed a propensity to penalize such content by generating fewer reactions to it.